Fluoxetine Dose and Administration Method Differentially Affect Hippocampal Plasticity in Adult Female Rats - Jodi L. Pawluski; Eva van Donkelaar; Zipporah Abrams; Virginie Houbart; Marianne Fillet; Harry W. M. Steinbusch; Thierry D. Charlier (Neural Plasticity)
Selective serotonin reuptake inhibitor medications are one of the most common treatments for mood disorders. In humans, these medications are taken orally, usually once per day. Unfortunately, administration of antidepressant medications in rodent models is often through injection, oral gavage, or minipump implant, all relatively stressful procedures. The aim of the present study was to investigate how administration of the commonly used SSRI, fluoxetine, via a wafer cookie, compares to fluoxetine administration using an osmotic minipump, with regards to serum drug levels and hippocampal plasticity. For this experiment, adult female Sprague-Dawley rats were divided over the two administration methods: (1) cookie and (2) osmotic minipump and three fluoxetine treatment doses: 0, 5, or 10 mg/kg/day. Results show that a fluoxetine dose of 5 mg/kg/day, but not 10 mg/kg/day, results in comparable serum levels of fluoxetine and its active metabolite norfluoxetine between the two administration methods. Furthermore, minipump administration of fluoxetine resulted in higher levels of cell proliferation in the granule cell layer (GCL) at a 5 mg dose compared to a 10 mg dose. Synaptophysin expression in the GCL, but not CA3, was significantly lower after fluoxetine treatment, regardless of administration method. These data suggest that the administration method and dose of fluoxetine can differentially affect hippocampal plasticity in the adult female rat.